Cardiac CT reveals high prevalence of coronary artery disease in esophageal cancer eligible for radiotherapy - Akinori Takada; Satoshi Nakamura; Yutaka Toyomasu; Takamitsu Mase; Tomoko Kawamura; Suguru Araki; Yoshitaka Suzuki; Masaki Ohi; Hajime Sakuma; Yoshihito Nomoto; Kakuya Kitagawa (Acta Oncologica)
Background: Assessment of cardiac disease before cancer therapy is crucial, as advancements in cancer treatment have led to prolonged survival and an increase in cardiovascular complications. Specifically, esophageal cancer and heart disease share common risk factors, such as smoking and obesity. Radiation therapy (RT) for esophageal cancer is associated with elevated cardiac radiation exposure. This study aimed to assess the prevalence of coronary artery disease (CAD) in patients with esophageal cancer who were eligible for RT.